DNA lesions and repair in trypanosomatids infection - Bruno M. Repolês; Carlos Renato Machado; Pilar T.V. Florentino (Genetics and Molecular Biology, 2020)
Abstract Pathological processes such as bacterial, viral and parasitic infections can generate a plethora of responses such as, but not restricted to, oxidative stress that can be harmful to the host and the pathogen. This stress occurs when there is an imbalance between reactive oxygen species produced and antioxidant factors produced in response to the infection. This imbalance can lead to DNA lesions in both infected cells as well as in the pathogen. The effects of the host response on the parasite lead to several kinds of DNA damage, causing alterations in the parasite’s metabolism; the reaction and sensitivity of the parasite to these responses are related to the DNA metabolism and life cycle of each parasite. The present review will discuss the survival strategies developed by host cells and Trypanosoma cruzi, focusing on the DNA repair mechanisms of these organisms throughout infection including the relationship between DNA damage, stress response features, and the unique characteristics of these diseases.